Sustainable use of Estonian peat reserves and environmental challenges - Orru, Mall; Orru, Hans (Estonian Journal of Earth Sciences, 2008)
Estonia is rich in peatlands, which cover 22.3% of its territory. About 1/4 of them are under protection, ~ 2% have been assigned for peat production, and ~ 1% is abandoned. Several peatlands are drained, which poses a challenge to their sustainability. The use of Estonian peat resources is regulated following the principles of sustainable management. During the inventory of Estonian peatlands (1971–1987) the properties (i.e. botanical composition) and quantity of peat were specified. In this paper an overview of these studies is given and new research fields focussing on chemical components of Estonian peat, i.e. trace elements, balneological characteristics, as well as the usability of the abandoned peatlands, are discussed.